A Randomized Trial of Urodynamic Testing before Stress-Incontinence Surgery - Nager, Charles W. (2012)
BACKGROUND: Urodynamic studies are commonly performed in women before surgery for stress urinary incontinence, but there is no good evidence that they improve outcomes. METHODS: We performed a multicenter, randomized, noninferiority trial involving women with uncomplicated, demonstrable stress urinary incontinence to compare outcomes after preoperative office evaluation and urodynamic tests or evaluation only. The primary outcome was treatment success at 12 months, defined as a reduction in the score on the Urogenital Distress Inventory of 70% or more and a response of “much better” or “very much better” on the Patient Global Impression of Improvement. The predetermined noninferiority margin was 11 percentage points. RESULTS: A total of 630 women were randomly assigned to undergo office evaluation with urodynamic tests or evaluation only (315 per group); the proportion in whom treatment was successful was 76.9% in the urodynamic-testing group versus 77.2% in the evaluation-only group (difference, −0.3 percentage points; 95% confidence interval, −7.5 to 6.9), which was consistent with noninferiority. There were no significant between-group differences in secondary measures of incontinence severity, quality of life, patient satisfaction, rates of positive provocative stress tests, voiding dysfunction, or adverse events. Women who underwent urodynamic tests were significantly less likely to receive a diagnosis of overactive bladder and more likely to receive a diagnosis of voiding-phase dysfunction, but these changes did not lead to significant between-group differences in treatment selection or outcomes. CONCLUSIONS: For women with uncomplicated, demonstrable stress urinary incontinence, preoperative office evaluation alone was not inferior to evaluation with urodynamic testing for outcomes at 1 year. (Funded by the National Institute of Diabetes and Digestive and Kidney Diseases and the Eunice Kennedy Shriver National Institute of Child Health and Human Development; ClinicalTrials.gov number, NCT00803959.)